2023
DOI: 10.1093/treephys/tpad025
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction alternation in trees: testing the resource depletion hypothesis using experimental fruit removal inQuercus ilex

Abstract: The key stones of resource budget models to explain mast seeding are that fruit production depletes tree stored resources, which become subsequently limiting to flower production the following year. These two hypotheses have, however, rarely been tested in forest trees. Using a fruit removal experiment, we tested whether preventing fruit development would increase nutrient and carbohydrates storage and modify allocation to reproduction and vegetative growth the following year. We removed all the fruits from ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…What determines masting and how predictable is it? Currently, we understand masting as a result of the interplay between weather and the internal resource dynamics of plants, and their combined impact on flower and seed development (Pearse et al, 2016;Pesendorfer et al, 2021;Bogdziewicz et al, 2020a;Roncé et al, 2023). Weather, as an external factor, has been demonstrated to impact various stages of the reproductive process, including flower initiation, pollination, and seed abortion (Kon & Noda, 2007;Koenig et al, 2015;Nussbaumer et al, 2020;Satake & Kelly, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…What determines masting and how predictable is it? Currently, we understand masting as a result of the interplay between weather and the internal resource dynamics of plants, and their combined impact on flower and seed development (Pearse et al, 2016;Pesendorfer et al, 2021;Bogdziewicz et al, 2020a;Roncé et al, 2023). Weather, as an external factor, has been demonstrated to impact various stages of the reproductive process, including flower initiation, pollination, and seed abortion (Kon & Noda, 2007;Koenig et al, 2015;Nussbaumer et al, 2020;Satake & Kelly, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…What determines masting and how predictable is it? Currently, we understand masting as a result of the interplay between weather and the internal resource dynamics of plants, and their combined impact on flower and seed development (Pearse et al ., 2016; Bogdziewicz et al ., 2020a; Pesendorfer et al ., 2021; Roncé et al ., 2023). Weather, as an external factor, has been demonstrated to impact various stages of the reproductive process, including flower initiation, pollination, and seed abortion (Kon & Noda, 2007; Koenig et al ., 2015; Nussbaumer et al ., 2020; Satake & Kelly, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…So far, Han et al [38] and Han and Kabeya [39], have shown that nitrogen (N) storage and mobilization is important for triggering flowering in Fagus . Fernandez-Martinez et al [40] and Le Roncé et al [41] have indicated that phosphorus (P) and zinc (Zn), and N and Zn, respectively are likely involved in mast fruiting of temperate trees more widely. Carbon should not be laid aside completely as a co-resource though.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al (2014) and Han and Kabeya (2017), for example, have shown that nitrogen (N) storage and mobilization is important for triggering flowering. Fernandez-Martinez et al (2017b) and Le Roncé et al (2023) have indicated that P and Zn, and N and Zn, respectively are likely involved in the mast fruiting of temperate forests. Carbon however should not be laid aside completely as a candidate resource as it usually operates in concert with N, phosphorus (P), potassium (K), and other elements, not just to build fruits and seeds but indirectly for growth and maintenance of other organs like roots for nutrient acquisition.…”
Section: Introductionmentioning
confidence: 99%